Stevie Smith and authorship - May, William, 1982- (Oxford : Oxford University Press, 2010)
This in-depth study of the British novelist, poet, and illustrator Stevie Smith (1902-1971) draws on extensive archival material to offer new insights into her work. May challenges conventional readings of her as an eccentric, and offers new perspectives on British 20th-century poetry and its reception.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Sept. 7, 2010).
Keywords: Smith, Stevie, -- 1902-1971 -- Criticism and interpretation